Device loss model of a fully SiC based dual active bridge considering the effect of synchronous rectification and deadtime - Wang, Zhenyu; Castellazzi, Alberto (2018)
It is becoming a great interest to employ SiC based power devices in dual active bridge (DAB) converter as an alternative to conventional Si-IGBT, due to its higher switching frequency potential, smaller switching losses as well as the capability to operate at synchronous rectification (SR) condition. This paper introduces the device loss model of a SiC MOSFET power module based DAB converter considering the effect of synchronous rectification, and the dead-time effect is also discussed. The calculated device loss for both SiC-MOSFET and Si-IGBT are discussed. The results show that the overall device loss is reduced by 40%, where the conduction loss is reduced by 38% because of SR capability of SiC-MOSFET, and the switching loss is reduced by 48% due to the faster transient of SiC-MOSFET during dead-time. On the other hand, the device losses are not even between the primary bridge and the secondary bridge of the DAB converter, and it is more significant for SiC-MOSFET based DAB due to the effect of SR with a maximum of 20%. At last, the dead-time range is given based on the device properties.